2016
DOI: 10.1007/s11207-016-0857-6
|View full text |Cite
|
Sign up to set email alerts
|

70 Years of Sunspot Observations at the Kanzelhöhe Observatory: Systematic Study of Parameters Affecting the Derivation of the Relative Sunspot Number

Abstract: Kanzelhöhe Observatory (KSO) was founded during World War II by the "Deutsche Luftwaffe" (The German Airforce) as one station of a network of observatories, which would provide information on solar activity in order to better assess the actual conditions of the Earth's ionosphere in terms of radiowave propagation. Solar observations began in 1943 with photographs of the photosphere and drawings of sunspots, plage regions and faculae, as well as patrol observations of the solar corona. At the beginning all data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…This would be a definite (for the X1.5) or an even more considerable (for the X2.0) improvement in determining the flare onset time, would a solar instrumentation measuring routinely LoS magnetic data in the chromosphere. A more comprehensive analysis of Korsós et al (2020a) has shown that, in spite of the apparent limitations of employing PF extrapolations only, the potential lead-time improvement for estimating the flare onset time varies in the interval (2,8) hours if one applies the WG M method to an identified "sunspot" in the height region between ∼800-1000 and ∼1800 km above the photosphere.…”
Section: Optimum Height For Forecastingmentioning
confidence: 99%
“…This would be a definite (for the X1.5) or an even more considerable (for the X2.0) improvement in determining the flare onset time, would a solar instrumentation measuring routinely LoS magnetic data in the chromosphere. A more comprehensive analysis of Korsós et al (2020a) has shown that, in spite of the apparent limitations of employing PF extrapolations only, the potential lead-time improvement for estimating the flare onset time varies in the interval (2,8) hours if one applies the WG M method to an identified "sunspot" in the height region between ∼800-1000 and ∼1800 km above the photosphere.…”
Section: Optimum Height For Forecastingmentioning
confidence: 99%
“…For the period from January 1945 to December 2004. Temmer et al (2006) derived HSNs from the daily sunspot drawings obtained at Kanzelhöhe Observatory (KSO, Austria;Pötzi et al 2016) 1 and Skalnate Pleso Observatory (Slovakia), and merged them to a common homogeneous data series. 2 The data coverage of daily observations from these two stations is 84% (see also, Rybák et al 2004).…”
Section: Datamentioning
confidence: 99%
“…当前(2020年), 我们已经 进入太阳活动第25周(1755年极小年为起点的太阳 活动周为第1周). [22] )的白光像对比了这两天中 黑子数量的多寡, 而日本Hinode卫星的软X射线像 则显示了黑子周围活动区辐射的强弱. 需要指出的 是, 短期的平静并非只能在太阳活动极小期才能见 到, 而短期的活跃也可以发生在太阳活动的衰减期 甚至极小期.…”
Section: -2unclassified